Desain Ulang Program Bantuan Dana Bergulir Di Kabupaten Sampang - Gigih Prihantono (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of microcredit is to encourage the growth of small and medium enterprise business and increasing prosperity by expanding public access to credit. Sampang Regency is one of the poorest regions in the East Java, where are very few microfinance institutions which provide the loan. However, 68% of the inhabitants have a loan that originated from informal sources (moneylenders, friends, or family), while only 5% who reported having a loan in the Bank. We are trying to help the local Government of Sampang to increased access of credit by redesigning Revolving Fund program (Dagulir) owned by the Government to increase the income of small and medium enterprise business. The results show that credit Dagulir can work widely through risk management and investment at the level of the household and not through their efforts as originally targeted.